2016
DOI: 10.1113/jp271573
|View full text |Cite
|
Sign up to set email alerts
|

Stochastic pacing reveals the propensity to cardiac action potential alternans and uncovers its underlying dynamics

Abstract: Key pointsr Beat-to-beat alternation (alternans) of the cardiac action potential duration is known to precipitate life-threatening arrhythmias and can be driven by the kinetics of voltage-gated membrane currents or by instabilities in intracellular calcium fluxes.r To prevent alternans and associated arrhythmias, suitable markers must be developed to quantify the susceptibility to alternans; previous theoretical studies showed that the eigenvalue of the alternating eigenmode represents an ideal marker of alter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 44 publications
1
17
0
Order By: Relevance
“…In this work, we investigate a simpler situation where the cycle length is drawn from a Gaussian distribution. Other numerical (58) and experimental (59) studies have observed that in single cardiomyocytes, even small amounts of variance in the pacing rate can contribute to the formation of cardiac alternans, with the resulting interpretation that HRV might be proarrhythmic. Based on the results to follow, we come to a different conclusion: on one-(1-D) and two-dimensional (2-D) domains with single-site pacing in simulations of healthy, homogeneous, and isotropic ventricular tissue, as the variance in the pacing rate increases, the propensity for the tissue to exhibit discordant alternans decreases.…”
Section: Introductionmentioning
confidence: 99%
“…In this work, we investigate a simpler situation where the cycle length is drawn from a Gaussian distribution. Other numerical (58) and experimental (59) studies have observed that in single cardiomyocytes, even small amounts of variance in the pacing rate can contribute to the formation of cardiac alternans, with the resulting interpretation that HRV might be proarrhythmic. Based on the results to follow, we come to a different conclusion: on one-(1-D) and two-dimensional (2-D) domains with single-site pacing in simulations of healthy, homogeneous, and isotropic ventricular tissue, as the variance in the pacing rate increases, the propensity for the tissue to exhibit discordant alternans decreases.…”
Section: Introductionmentioning
confidence: 99%
“…The increased fluctuations seen as one approaches a period‐doubling bifurcation have been very recently considered in two situations using interventions that are capable of provoking arrhythmias: fast pacing (Prudat et al . in this issue) and administration of a potassium channel blocker (Quail et al . ).…”
Section: Photograph Of the Organisers Of The Mines Centennial Symposiummentioning
confidence: 99%
“…In a similar vein, in this issue Trayanova & Chang (2016) describe how one can use MRI mapping, combined with computer simulation, to determine the risk for ventricular tachycardia and fibrillation and to help guide ablations in the clinic, while Jacquemet (2016) discusses modelling of six different targets for ablation in atrial fibrillation. The increased fluctuations seen as one approaches a period-doubling bifurcation have been very recently considered in two situations using interventions that are capable of provoking arrhythmias: fast pacing (Prudat et al 2016 in this issue) and administration of a potassium channel blocker (Quail et al 2015). In a perspective on the former article in this issue, Vandenberg & Hill (2016) suggest that analysis of cardiac alternans might be useful in improving management of patients at risk for sudden cardiac death.…”
Section: Emerging Areas and Prospectsmentioning
confidence: 99%
“…In general, mathematical and physical perspective has led to models that may study physiological mechanisms [4], through the analysis of several variables with mathematical and physiological implications [5]. Symbolic dynamics for the cardiac dynamic variability have been studied [6,7].…”
Section: Introductionmentioning
confidence: 99%